Synthesis and Identification of Some New Derivatives of Benzoxazole Bearing Pyrazole and 1, 2, 4-Triazine Rings - Ahmed S. Hamed (Journal of Global Pharma Technology, 2020)
In this work, new derivatives of benzoxazole bearing two types of heterocyclic rings; pyrazole and 1,2,4-triazine have been described. This work involved preparation hydrazide derivative 5 as a key material in the synthetic route, which was obtained over five sequence steps. Reaction of 2-aminophenol with CS2 under basic conditions afforded 2-mercaptobenzoxazole 1 in 61% yield.  Michael addition of 1 to ethyl acrylate provided the desired ester 2 in a good yield (74%). Thereafter, hydrolysis of the ester group at 2 using basic conditions yielded the corresponding acid 3. The acid 3 was then converted to acid chloride 4, followed by nucleophilic addition of hydrazine hydrate was performed in a one-pot reaction and provided the desired hydrazide 5 in a 71% yield. Pyrazole derivatives 6-11 were then obtained via reaction of 5 with 1, 3-dicarbonyl compounds. Whereas, treatment of 5 with 1, 2-dicarbonyl compounds and NH4OAc in the presence of K2CO3 as a base gave the desired 1, 2, 4-triazine derivatives 12-17.        Keywords: Benzoxazole, Anticancer, 1, 2, 4-Triazine ring, Heterocyclic.